(untitled) (Journal of Informatics Education and Research, 2024)
The Government of India’s National Education Policy (NEP) 2020 places a strong emphasis on internationalization and foreign collaborations in higher education. NEP 2020 is a powerful instrument for building worldwide collaborations because of its innovative approach to internationalization. The policy encourages cooperation through initiatives including combined degree programs, academic mobility, and research alliances with respectable foreign universities. It facilitates the process for foreign universities to establish campuses in India and encourages Indian institutions to increase their global presence. By promoting credit transfer programs and reciprocal qualification recognition, NEP 2020 aligns Indian education with global standards. This research examines the ways in which NEP 2020 has enabled these collaborations, pinpoints obstacles, and assesses their consequences for higher education in India. Both quantitative and qualitative techniques were used to assess a sample of 117 academic institution respondents. To guarantee thorough results, statistical testing and hypothesis validation were carried out. This study also examined the effects of NEP 2020 on international partnerships in Indian higher education, assessed the results, and pinpointed solutions to problems. The results advance knowledge of how policy frameworks improve HEIs’ internationalization and competitiveness in the global market.